PENGARUH METODE PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PRESTASI BELAJAR DITINJAU DARI GAYA BELAJAR DAN KEMANDIRIAN - Sigit Sujatmika (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2016)
The aims of this research were to find out: (1) the effect of learning method by applying Problem Based Learning toward the student’s achievement. (2) The effect of learning style toward student’s achievement. (3) The effect of independence toward the student’s achievement. (4) The interaction between the learning style and independence toward the students’ achievement. This research used experimental method. The population was the students of  Primary School Education Program in semester 4 school year 2011/2012 by eight classes. Two classes were taken as the samples by applying cluster random sampling technique. Student’s achievement were collected by using test method, while the student’s learning style and student’s independence was collected by employing questionnaire method. The data analysis technique used was a three way analysis of variance with unequal cells (ANOVA). The results were: (1) there was no influence of Problem Based Learning methods toward student’s achievement (p=0.620). (2) There was no influence of learning style by visual, auditorial, and kinestetic toward students’ achievement (p=0.455). (3) There was no influence of high and low of student’ independence toward the students’ achievement (p=0.703). (4) There was no interaction between the learning style and the student’s independence toward the students’ achievement (p=0.708). Keywords : Problem Based Learning, Learning style, Independence